Medical expenditure after marginal cut of cash benefit among public assistance recipients in Japan: natural experimental evidence. Issue 5 (12th November 2021) - Nishioka, Daisuke; Takaku, Reo; Kondo, Naoki
Abstract : Backgrounds: Income reduction in poor households affects healthcare demands for impoverished population. However, the impact of reduced benefits for public assistance recipients, who can use medical services for free, on healthcare costs has not been examined. We hypothesised that marginal cuts in benefits increase recipients' medical expenditure by extra demand for medical care. We tested this hypothesis using public assistance databases of Japan. Methods: The study population comprised households in five municipalities receiving public assistance between April 2016 and September 2018. The households have a child aged 12–60 months and receive a monthly child-support income of US150, which reduces by US50 when the child turns 36 months of age. Our analysis comprised an age-based sharp regression-discontinuity study. Results: We observed 4893 household-months (11 032 person-months). When a firstborn child reached 36 months, their frequency of outpatient visits and healthcare costs by recipients, except for the firstborn child, increased (0.45, 95% CI: 0.30 to 0.61; US111.2, 95% CI: 20.7 to 201.7), while those of the firstborn child did not increase significantly. The monthly medical expenditure per household increased by US248.6 (95% CI: 25.4 to 471.7). Inpatient medical costs increased significantly (US64.3, 95% CI: 8.4 to 120.2). Conclusions: Government savings through income reduction were offset by increased medical expenditure. This may be due to recipients' behavioural change and their worsening health conditions. To prevent excessive medical expenditure, policymakers should consider how income reduction affects the behaviour and health of the impoverished population.